Quem faz nossas roupas? Análise do documentário The true cost (2015) e do acordo de Bangladesh - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The main objective of the present study is to verify whether the responses to the complaints of labor rights violations presente in the filmic source were effective in improving the working conditions of workers in Bangladesh. So, we critically analyzed the documentar The True Cost (2015) and what was done after the Rana Plaza acidente to ensure the protection of workers in the textile chain in the country using the inductive method and the documentary empirical approach method. From this analysis, it was possible to conclude that the Bangladesh Accord, signed after the Rana Plaza events, was insuficiente tto guarantee the protection of workers in the country, since not all the inspected factories were able to implement the remediation plans provided for the Accord, in the same way, it leaves some gaps on the issue of labor outsourcing and on how the inspection will be carried out when the inspections are under the responsability of the Government of Bangladesh.
Who makes our clothes? Analysis of the documentary The true cost (2015) and the Bangladesh agreement
Keywords: The True Cost; Rana Plaza; Acordo de Bangladesh; Bangladesh Accord; CNPQ::CIENCIAS SOCIAIS APLICADAS